PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN KURIKULUM MERDEKA BELAJAR - Evy Ramadina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2021)
The objective of this research is to describe an overview of headmaster in the development of an self regulated learning curriculum. This research is a qualitative research with literature study method. Data analysis used the Miles and Huberman model. Research data obtained from documentation. The findings of the study indicate that: (1) the principal performs the role of supervisor and leader of change in his educational institution, (2) the independent learning curriculum is a student-centered educational program planning, where the education unit has autonomy in curriculum development, (3) the principal Schools have a strategic role in the curriculum development process.